PENINGKATAN HASIL BELAJAR SISWA KELAS V SDN 09 KUBU DALAM MATA PELAJARAN PAI PADA MATERI MENGENAL KITAB-KITAB ALLAH MELALUI STRATEGI GALLERY OF LEARNING - Yanti Yanti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
This research is a classroom action research conducted in the fifth grade of the 9 Kubu State Elementary School in the subject of Islamic religious education. This research is based on the problem of not achieving completeness of student learning outcomes in accordance with KKM standards. It is suspected that the learning strategies applied so far are still teacher-centered learning, especially in the form of conventional lectures and proposing questions and answers. In addition, the classroom atmosphere is also passive, namely the lack of student involvement in the learning process. This classroom action research aims to improve student learning outcomes with the Gallery of Learning strategy. This research was conducted in two cycles. Based on the results of classroom action research conducted on fifth grade students at SDN 9 Kubu, it can be concluded that learning with the Gallery of Learning Method in the subject of Islamic religious education in the material Knowing the books of Allah Swt can improve student learning outcomes which are marked by an increase in complete learning Learners in each cycle, namely; 72.91% in cycle 1 and 84.16% in cycle 2.